Lessons from a Community-Based Participatory Research Project: Older People's and Researchers' Reflections - TIMONEN, VIRPI; DOYLE, MARTHA (My University, 2010)
The ethical and practical importance of actively involving older people in the research process is increasingly articulated in the gerontology literature. This article contributes to the literature by outlining a community-based participatory research project that centered on the design and administration of a questionnaire exploring older people?s use and perceptions of community services. The authors discuss both older adults? and the researchers? views of the participatory process. The key lessons and challenges that emerged from the research are analyzed using the nine principles of community-based participatory research outlined by Israel et al. The authors question whether older people in all instances seek extensive involvement in all aspects of participatory projects and raise a number of questions that require further analysis before a robust and viable understanding of participatory research that safeguards against the tokenistic involvement of older people can be developed.
PUBLISHED
Keywords: participatory; research; older people; community; partnership; power